CATALYSTS FOR THE GAS-PHASE OXIDATION OF ETHYLENE AND ACETICACID TO VINYL ACETATE AND METHOD FOR PRODUCTION AND USE THEREOF - DAMBECK, GUNTER; KUHLEIN, KLAUS; WEIDLICH, STEPHAN; GEISS, GERHARDT; RUTSCH, ANDREA; DINGERDISSEN, UWE; WERNER, HARALD; HAGEMEYER, ALFRED (2009)
The invention relates to a supported catalyst and the production and use thereof in the synthesis of vinyl acetate in the gaseous phase from ethylene, acetic acid and oxygen, or from gases containing oxygen, whereby the activity and selectivity are simultaneously improved. The catalyst contains palladium, at least one alkali metal compound and optionally one or more catalyst accelerators, in particular, gold, barium and/or cadmium on a porous support. Said support contains at least on e reducible metal oxide, in particular oxides of the elements of groups IIIb, IVb, Vb, VIb from the periodic table of elements. Once the support has been loaded with at least one palladium compound, a reduction is carried out at a temperature of > 200 .degree.C.